Análise do comportamento da frequência cardaca fetal durante a realização de cirurgia a céu aberto para correção de mielomeningocele - Santana, Eduardo Felix Martins [UNIFESP] (2015)
Objective: To access left ventricle modified myocardial performance index (MPI) during open fetal surgery. Methods: Open myelomeningocele repair was performed in 37 fetuses between the 24th and 27th week of gestation. MPI-mod was claculated at specific periods: pre-anesthesia (1), post-anesthesia (2), neurosurgery (3a-early skin manipulation, 3b- spinal cord releasing and 3csintesis), and end of surgery (4). deviation (SD) of MPI and its related times- isovolumetric contraction time (ICT), isovolumetric relaxation time (IRT) and ejection time (ET), was determined for each period. ANOVA with repeated measures was used to assess differences among these periods. Tukey multiple comparation test compared global surgery stages. Results: The of MPI in the specific time points were 0.32 ( 06); 0.32 05); 0.34 05); 0.48 10); 0.36 06) e 0.32 .05), respectively (p<0.001). In the two-tailed time comparisons, neurosurgery stage presents MPI highest levels, especially on stage 3b, related to ICT and IRT rising and ET decreased levels. Conclusion: Fetal global cardiac function is altered during the open MMC repair. The neurosurgery stage represents the critical moment of the procedure.